The Tuxá indigenous social network, interaction and exchange of information for the promotion of adaptive measures in the face of climate change (Sustainability in Debate, 2022)
Studies show Social Network Analysis (SNA) as a successful methodology within the environmentalsciences. In the present study, this methodology was implemented in the Tuxás indigenous communityin Bahia-Brazil, to understand the configuration of interaction and information flow of the people andtheir multilevel relationship to face the environmental problem of drought. By creating networks byscale, we identify actors and their roles within the community, characterising the centrality of actorsand their internal and external relationships to create adaptive strategic actions that strengthen thelinks between them and local and regional initiatives. For data collection, structured interviews wereconducted with key informants using the snowball methodology. As a result, the SNA made it possibleto identify links, bottlenecks and potential institutions to reduce the vulnerability of the traditionalpopulation and to identify adequate ways to promote adaptation and solve environmental problems.